Two new loci, PLEIADE and HYADE, implicate organ-specific regulation of cytokinesis in Arabidopsis - Müller, Sabine; Fuchs, Esther; Ovecka, Miroslav; Wysocka-Diller, Joanna; Benfey, Philip N.; Hauser, Marie-Theres (Plant Physiology, 2002)
In screens for regulators of root morphogenesis in Arabidopsis we isolated six new recessive mutants with irregular cell expansion. Complementation analyses placed the mutations in two loci, PLEIADE (PLE) and HYADE (HYA). Phenotypic analyses revealed multinucleated cells, cell wall stubs, and synchronized cell divisions in incompletely separated cells that are all characteristics of defective cytokinesis. These defects were pronounced in roots and undetectable in aerial organs. In addition, fertility and germination were not affected by the mutations. Thus, the alleles that we have isolated of PLE and HYA suggest that the genes may encode organ-specific components needed primarily during root development. Analysis of microtubule arrays during cell cycle in ple and hya roots indicates that the presence of several synchronized nuclei influences the position of preprophase band, mitotic spindles, and phragmoplasts. The enhanced and synergistic phenotype of PLE/ple.hya/hya seedlings and double mutants point to a role of PLE and HYA in the same process. These mutants provide tools to elucidate the regulation of nuclear cytoskeletal interactions during cell division and cytokinesis.
Created from Fastlane, Scopus look-up